The Fixed Point Theory for Some Generalized Nonexpansive Mappings - Enrique Llorens Fuster; Elena Moreno Gálvez (Abstract and Applied Analysis)
We study some aspects of the fixed point theory for a class of generalized nonexpansive mappings, which among others contain the class of generalized nonexpansive mappings recently defined by Suzuki in 2008.